Poster Elektronik Iklan Layanan Masyarakat Bahaya Stress Pada Remaja - M. Dimas Syahputra; Heldi Heldi (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Stress can be defined as a physiological and psychological response that occurs when individuals experience pressure or burdens that exceed their ability to cope. Stress in adolescents can be caused by various influencing factors such as academic demands, family problems, conflicts with peers, teenage romance and identity problems. However, teenagers still have a low understanding of the dangers of stress, in addition to the lack of optimal information through public service advertisements, especially for teenagers. The aim of the design is to build an "Electronic Poster for Public Service Advertisements about the Dangers of Stress that is informative, communicative, educative, effective and easy to understand for teenagers aged 10-18 years in Padang City." This design method uses the glass box method, namely a design method that is carried out rationally and logically on the work based on the information obtained, based on: analytical, synthetic and evaluative to get the best solution. The approach uses 5W+1H analysis (what, when, where, who, why, how). Results of designing the main media for Electronic Posters for Public Service Advertisements about the Dangers of Stress in Adolescents and supporting media: leaflets, flayers, social media, x-banners, tote bags, t-shirts and stickers. This design can provide creative thinking visually, informatively, communicatively, educatively and effectively for teenagers aged 10-18 years.